Typological mapping of thermal comfort : The role of urban green space and carbon emissions - Dewi, Arifima Nurlaila; Kurniawan, Andri; Wibisono, Hafidz (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2026)
The massive growth of urban areas in the Depok subdistrict has triggered microenvironmental degradation, which has resulted in a decrease in the thermal comfort of the community. This study aims to identify the level of vegetation density of Public Green Open Space (GOS), map CO2 emission hotspots and thermal comfort (THI), and analyze the typology of the relationship between these variables. The method used is quantitative descriptive with the integration of remote sensing (NDVI Landsat 8) and spatial modeling. This study presents an original approach through a spatial typology analysis framework that synergizes THI, NDVI, and CO2 emission variables to analyze the complexity of microclimate phenomena in urban areas in depth. The findings show that the study area is dominated by the Comfortable-Low Emission typology (28.93%), especially in areas with high vegetation density. However, an urban heat island phenomenon was found in the critical zone of 0.56% which forms a thermal hotspot due to the effect of the urban canyon on the commercial area. Other findings show the typology of the THI and NDVI relationship dominated by the Comfortable-Low NDVI typology (24.74%), covering more than 52% of the area thanks to the support of 28 Public Green Open Space points and the campus forest on the west side. Conversely, critical areas with an Uncomfortable-Low NDVI typology (1%) are concentrated in commercial areas. Therefore, a government strategy is needed to prioritize protecting rice fields and adding shade vegetation in commercial areas.